Effect Of 30 s Of Static Active Stretching On Anaerobic Power Using The Wingate Test - Kazushige, Oshita (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe